2017
DOI: 10.1177/0037768617727482
|View full text |Cite
|
Sign up to set email alerts
|

The lived religion approach in the sociology of religion and its implications for secular feminist analyses of religion

Abstract: approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…This framework implies that a disaggregated, multidimensional conceptualization of religiosity is needed, instead of focusing on differences between Muslims and non-Muslims, as previous studies have done (e.g., Inglehart and Norris 2003 ; Lussier and Fish 2016 ; Norris 2009 ). This is because rigid patriarchal religious structures obstruct support for gender equality while other dimensions of religiosity stimulate emancipatory advancements (see Cornwall et al 1986 ; Hall 1997 ; Nyhagen 2017 ; Stark and Glock 1968 ). Indeed, our results consistently showed that while religious service attendance, textualism, and devotion decreased support for gender equality, the salience of religious beliefs in life choices had no singularly negative impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This framework implies that a disaggregated, multidimensional conceptualization of religiosity is needed, instead of focusing on differences between Muslims and non-Muslims, as previous studies have done (e.g., Inglehart and Norris 2003 ; Lussier and Fish 2016 ; Norris 2009 ). This is because rigid patriarchal religious structures obstruct support for gender equality while other dimensions of religiosity stimulate emancipatory advancements (see Cornwall et al 1986 ; Hall 1997 ; Nyhagen 2017 ; Stark and Glock 1968 ). Indeed, our results consistently showed that while religious service attendance, textualism, and devotion decreased support for gender equality, the salience of religious beliefs in life choices had no singularly negative impact.…”
Section: Discussionmentioning
confidence: 99%
“…In line with classic and more contemporary distinctions, we firstly differentiate between (external) religious practices and (internal) religious beliefs (see Figure 1 ) ( Cornwall et al 1986 ; Hall 1997 ; Kellstedt et al 1996 ; Stark and Glock 1968 ). We further subdivide religious practices into two categories: private religious behaviors that are acted out without others, and communal practices, such as attending religious services, that imply exposure to the institutional patriarchal establishment’s home ( Aune 2015 ; Mir-Hosseini 2006 ; Nyhagen 2017 ). Concerning religious beliefs, a further distinction can be made as well.…”
Section: Religious Socialization Reconsideredmentioning
confidence: 99%
“…can be considered in dialogue with feminist theorisations of the secular. Similar to feminist scholars who pose questions about how to envision alternative and inclusive political-societal futures (Aune et al 2017;Nyhagen 2017;Reilly 2017), BOEH! does not provide an easy answer.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, religious studies have engaged with discussions on the existing gap between normative ideals and praxis, referred to as a "lived religion" approach (Nyhagen 2017). Instead of concentrating predominantly on the study of religious institutions and organizations, this approach considers the experience of religious persons in everyday life (Orsi 2003), assuming that people have an active and reflexive role in changing and negotiating their spiritual practices and beliefs, as well as engaging with institutional forms of religion.…”
Section: Women In Sikhism In Theory and In Practicementioning
confidence: 99%